Advection and scavenging controls of Pa/Th in the northern NE Atlantic. (30th June 2014) - Roberts, Natalie L.; McManus, Jerry F.; Piotrowski, Alexander M.; McCave, I. Nicholas
Abstract Over the last 2 decades, significant advances have been made in reconstructing past rates of ocean circulation using sedimentary proxies for the dynamics of abyssal waters. In this study we combine the use of two rate proxies, sortable silt grain size, and sedimentary 231Pa/230Th, measured on a depth transect of deep‐sea sediment cores from the northern NE Atlantic, to investigate ocean circulation changes during the last deglacial. We find that at two deep sites, the core‐top 231Pa/230Th ratios reflect Holocene circulation rates, while during Heinrich Stadial 1, the deglacial ratios peaked as the sortable silt grain size decreased, reflecting a general circulation slowdown. However, the peak 231Pa/230Th significantly exceeded the production ratio in both cores, indicating that 231Pa/230Th was only partially controlled by ocean circulation at these sites. This is supported by a record of 231Pa/230Th from an intermediate water depth site, where values also peaked during Heinrich Stadial 1, but were consistently above the production ratio over the last 24 ka, reflecting high scavenging below productive surface waters. At our study sites, we find that preserved sediment component fluxes cannot be used to distinguish between a scavenging or circulation control, although they are consistent with a circulation influence, since the core at intermediate depth with the highest 231Pa/230Th recorded the lowest particle fluxes. Reconstruction of advection rate using 231Pa/230Th in this region is complicated by high productivity, but the data nevertheless contain important information on past deep ocean circulation.